Association of clinicopathological factors and treatment modalities in the recurrence of ameloblastoma: Analysis of 624 cases. (16th August 2021) - Goh, Yet Ching; Siriwardena, Bogahawatte Samarakoon Mudiyanselage Samadarani; Tilakaratne, Wanninayake Mudiyanselage
Abstract: Background: Ameloblastoma is an odontogenic tumour exhibiting locally invasive behaviour and high recurrence rate after treatment. Conventional ameloblastoma is reportedly been more aggressive showing infiltrative growth patterns and a tendency for recurrence. This is a retrospective study performed to analyse the relationship between clinicopathological characteristics and treatment modalities in the recurrence of ameloblastoma. Methods: 624 cases of ameloblastoma comprising of 519 non‐recurrent ameloblastoma and 105 recurrent ameloblastoma from two main diagnostic centres in Malaysia and Sri Lanka were included. The demographic data, clinical characteristics, histopathological data, treatment modality and episodes of recurrence were extracted and analysed. Results: The mean age for recurrent ameloblastoma was 37.23 with a peak occurrence in the third decade of life. Recurrent ameloblastoma was marginally female predominant with male to female ratio of 1:1.3. Mandible was the commonest site for the recurrence with a predilection for more than two segments of left mandible followed by left posterior mandible. Follicular (58.1%) histopathological variant was the most reported type to recur followed by plexiform (17.1%). 49.5% of recurrent cases were treated with conservative approach. 65.7% of recurrent cases demonstrated a single episode of recurrence. Mixed (follicular and plexiform) histopathological variants showed the longest average years (11.5 years) for the single episode of recurrence. Plexiform ameloblastoma treated with conservative approach recurred in the shortest follow‐up period. The recurrence of ameloblastoma was significantly associated with age group, sub‐site of occurrence and histopathological variants ( p <0.05). Conclusion: This study showed that age, sub‐site of occurrence and histopathological variants are significant factors responsible for the recurrence of ameloblastoma.